The Effectiveness of Mechanical Power on An Auxiliary Rotor in The Design of Counter Rotating Wind Turbine (CRWT) - Huda, Luqman Al; Evan, Bah; Prasetya, Ari; Sandi, Dianisa Khoirum; Prihatmini, Eri; Fajri, Amrisal Kamal (Politeknik Negeri Semarang, 2025)
The counter-rotating wind turbine (CRWT) represents a novel development in horizontal-axis wind turbine technology. This innovative design incorporates an additional rotor that rotates in unison with the main rotor along the same axis. Without the supplementary rotor, the turbine's configuration is analogous to that of a horizontal-axis wind turbine (HAWT) with the main rotor functioning independently. The primary objective of this study is to undertake a comparative analysis of the effectiveness of mechanical energy generation, as measured by torque, between the CRWT and HAWT designs. The configuration of the wind turbine is situated within a wind tunnel, characterized by a rectangular cross-section. The testing of wind turbines has been conducted at wind velocity of 2 m/s, 3 m/s, and 4.5 m/s. The total mechanical power measured was 0.14 W, 0.21 W, and 0.28 W at wind velocity of 2 m/s, 3 m/s, and 4.5 m/s, respectively. The final results of the study have analyzed the effectiveness of power enhancement through power coefficients.